Factor XI deficiency as a clinical problem in labor - a case report - Adamczyk-Gruszka, Olga; Zwierzyńska, Anna; Płusajska, Justyna; Gruszka, Jakub (Journal of Education, Health and Sport, 2022)
Hereditary factor XI deficiency has been a mystery since its discovery in 1953. The most common mild symptoms in patients with the most severe form do not match the abnormalities in standard clotting tests. The contribution of factor XI to hemostasis is not adequately assessed in modern clinical laboratories. How does factor XI deficiency contribute to changes in blood clotting patterns, what is the genetics of this condition, and the relationship between its deficiency and bleeding? A new approach of gynecologists to childbirth in patients with factor XI deficiency. This article describes the case of a pregnant woman with hemophilia C.